Customer participation and service outcomes: Mediating role of task-related affective well-being - Asokan, A.; Sharma, Piyush; Kingshott, Russel; Kaur, A.; Maurya, U. (Emerald Group Publishing, 2018)
This paper contributes to transformative service research by drawing on self-determination, elicitation of emotions framework, and feelings-as-information theories to explore how customer participation, task-related affective well-being, customer knowledge, task complexity, and service outcomes relate with each other. Design/methodology/approach-A synthesis of relevant literature on customer participation and customer well-being reveals a conceptual model with eleven testable propositions. Findings-The conceptual model shows that task-related affective well-being mediates the link between customer participation and service outcomes. Moreover, customer knowledge and task complexity moderate these links. Research limitations/implications-An empirically testable conceptual model models the roles of task-related affective well-being, customer knowledge and task complexity in the process by which customer participation influences service outcomes. Practical implications-Service managers can use the model to design services based on the effects of different types of customer participation on task-related affective well-being. Originality/value-This paper is one of the first to study the mediating role of task-related affective well-being in the relationship between customer participation and service outcomes. It does so by revealing the differential impact various types of participation have on service outcomes and the moderating role of customer knowledge and task complexity.